Prediksi Understandability Pada CK Metrics Object Oriented Menggunakan Fuzzy Inference System - Hertyana, Hylenarti; Fauzi, Ahmad (LPPM UNIKA Santo Thomas Medan, 2020)
The ability of the software to easily understand it is very important, to evaluate the performance of a system or process a certain mechanism is needed. So that the achievement level of software development is obtained, the assessment of code quality and design in the metrics have different contributions to the quality properties of software design. The assessment of software characteristics is described in a model based on the Chidamber Kemerer (CK) Entropy Metrics design property indicator. Measure specific properties of the software by mapping them into numbers according to objective and well-defined measurement rules. To be able to help perform the software quality calculation process based on CK metrics on the eclipse equinox data by using the Mamdani fuzzy inference system, pointing the classification into low which can be interpreted as having good quality. And the value affirmation of the deffuzzyfication method in this case is done by using the COA (center of area) method, to determine the crisp x value, obtained from the membership function formed from the composition process of all outputs.